Role of hematological parameters and biochemical markers as a predictor of severity of COVID-19 patients - Sanjuna D,; Nikita Singh,; Gautam Chandrakoshi,; Rashmi Jain,; Ankit Jain, (Asian Journal of Medical Sciences, 2022)
Background: The etiological agent for pandemic COVID-19 is severe acute respiratory syndrome corona virus 2. Hematological and biochemical parameters are the indicators of inflammation and coagulopathy. Aims and Objectives: The present study aimed to determine how effectively the hematological parameters and biochemical markers can help predict the severity of critically ill COVID-19 patients. Materials and Methods: The current retrospective cohort study was conducted among 200 COVID-19 patients admitted in the Sanjay Gandhi Memorial Hospital, Rewa, Madhya Pradesh, India. In our lab’s computerized system, certain hematological and biochemical parameters of the patients were retrieved and recorded. Receiver operating characteristics (ROC) curve analysis was done to evaluate the diagnostic accuracy of hematological and biochemical parameters. Results: Total leukocyte count (TLC), absolute lymphocyte count (ALC), neutrophil to lymphocyte ratio (NLR), D-dimer, and serum ferritin had a significant relationship with severity among ICU patients (P<0.05). ALC, D-dimer, and serum ferritin can be used to predict the severity of COVID patients with area under the ROC-AUC curve values of 0.717, 0.725, and 0.710, respectively. Platelet to lymphocyte ratio, lymphocyte to monocyte ratio, and C-reactive protein were not useful to predict the severity of COVID illness. Conclusion: Hb concentration, TLC, NLR, D-dimer, and serum ferritin were significantly raised in critically ill COVID patients. ROC curve analysis showed that ALC, serum ferritin, and D-dimer were able to predict the severity of COVID illness effectively. Conclusively, these parameters can be used to track the prognosis of patients.